Analisis Pelaksanaan Akreditasi Lembaga Pelatihan Kerja di Dinas Tenaga Kerja dan Transmigrasi Provinsi Sumatera Selatan Tahun 2021 - Damayanti, Fitriah; Syuroh, Mat; Sandy, Amiruddin (@-Publik: Jurnal Administrasi Publik, 2023)
The purpose of this study was to analyze the implementation of the Accreditation of Job Training Institutions at the Manpower and Transmigration Office of South Sumatra Province in 2021. The type of data used in this research is included in the type of qualitative data obtained from interviews with informants, besides that this research also refers to books , regulations, documents, journals and other literature that are considered relevant to this research. This study uses G.R Terry's theory using management functions namely Planning, Organizing, Actuating and Controlling. The first dimension is Planning, both in terms of Human Resources planning who already have competence in their respective fields, as well as from planning the implementation of well-planned activities, starting from the implementation of technical guidance on accreditation until the plenary meeting is held. The second dimension is that the organization can be said to be good, because the Office of Manpower and Transmigration of South Sumatra Province, KA-LPK and the team of assessors have carried out their duties assigned to people according to their abilities, and allocated resources, and coordinated them in the accreditation activities.